Genetics in familial hypercholesterolaemia – from genetic research to new guidelines - Prokop, Edyta Kinga; Jagodziński, Paweł Piotr; Grajek, Stefan (Journal of Medical Science, 2019)
Familial Hypercholesterolaemia (FH) is genetic disorder touching up to 1 to 250 people, increasing the risk of atherosclerotic cardiovascular disease risk and early death by 3–13 times. The majority of mutations are autosomal dominant among 3 genes related to cholesterole metabolism: LDL‑receptor (LDLR), apolipoprotein B (APOB) or proprotein convertase subtilisin/kexin type 9 (PCSK9). It comprises 60% of reported cases, which still is not at satisfactory level. This article summarizes new research in the field of FH and points out new therapeutic methods — PCSK9 inhibitors as advised in new European Society of Cardiology guidelines od dyslipidaemias.